2011
DOI: 10.1111/j.1349-7006.2011.02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Early activation and interferon‐γ production of tumor‐infiltrating mature CD27high natural killer cells

Abstract: Natural killer (NK) cells are known to be critically involved in the control of tumors through their direct cytotoxic function, but have also been proposed as an initial source of interferon (IFN)‐γ that primes subsequent adaptive tumor‐specific immune responses. Although mounting evidence supports the importance of NK cells in antitumor immune responses, the immunological characteristics of NK cells infiltrating the tumor microenvironment and the mechanisms that regulate this process remain unclear. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
(95 reference statements)
1
23
0
Order By: Relevance
“…It has been found that IFN-g plays a critical role in NK cells infiltration into the local tumor site and the tumor-infiltrating NK cells mainly suppresses tumor progression through the IFN-g pathway (Hayakawa et al, 2011). In this study, blocking IFN-g by anti-IFN-g neutralizing Ab not only inhibited TRAIL expression, but also down-regulated the tumoricidal activity of NDVstimulated NK cells (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…It has been found that IFN-g plays a critical role in NK cells infiltration into the local tumor site and the tumor-infiltrating NK cells mainly suppresses tumor progression through the IFN-g pathway (Hayakawa et al, 2011). In this study, blocking IFN-g by anti-IFN-g neutralizing Ab not only inhibited TRAIL expression, but also down-regulated the tumoricidal activity of NDVstimulated NK cells (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…5 Despite the infiltration of cytotoxic NK cells in the tumor microenvironment, tumors continue to grow, suggesting that the tumor microenvironment, which includes stromal cells and tumor-derived factors, can modulate the phenotype and function of NK cells. Pietra et al have demonstrated that melanoma cell lines inhibit the cytolytic activity of NK cells in vitro and that this impairment was mediated by melanoma cells-derived IDO (Indoleamine 2, 3-dioxygenase) and PGE2 (Prostaglandin E2).…”
Section: Cd11bmentioning
confidence: 99%
“…4 Infiltration of NK cells has been observed in several types of tumors such as fibrosarcoma, renal cell carcinoma, gastrointestinal sarcoma, and breast tumors. 5,6 The CD27…”
Section: Cd11bmentioning
confidence: 99%
“…IFN-γ is confirmed to possess immune-activating properties and hence is proven to have anti-cancer effects in vivo (Wakita et al, 2009;Hayakawa et al, 2011, Yuan et al, 2014. In addition, recent studies also have indicated that IFN-γ has the ability to directly inhibit cancer cell growth (Tate et al, 2012;Liu et al, 2012;Jin et al, 2013;Zhao et al, 2013;Wang, 2014); however, the mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ is a major activator of various types of immune cells (Wakita et al, 2009;Hayakawa et al, 2011) and also can induce the expression of the major histocompatibility complex in both normal and malignant cells and provokes inflammatory 1 infiltrate infiltration (Chen et al, 2012;Hong et al, 2014). In addition, IFN-γ can directly inhibit the growth of cells, in some cases, through the induction of cell cycle arrest with or without the concomitant induction of apoptosis (Tate et al, 2012;Liu et al, 2012;Jin et al, 2013;Zhao et al, 2013Wang, 2014.…”
Section: Introductionmentioning
confidence: 99%